2014
DOI: 10.1177/2158244014550618
|View full text |Cite
|
Sign up to set email alerts
|

Group Therapy for Adolescents Living With an Eating Disorder

Abstract: Group models are commonly used to treat eating disorders; however, research in this area remains largely underdeveloped. Interest in group work is likely to increase due to the demands on the public health system and the cost-effectiveness of group modalities. This scoping review sought to explore the evidence underpinning group therapy for adolescents living with an eating disorder. A literature search of 10 academic databases and four gray literature databases was undertaken in 2013. Selected Internet resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…En 2014 se publica una revisión sobre los tratamientos en grupo de adolescentes con TCA, donde queda reflejado la escasez de estudios con un buen diseño en este ámbito. Se encontró que los grupos de terapia conductual cognitiva eran más efectivos para la bulimia nerviosa y la terapia grupal multifamiliar mostró ser prometedora para la anorexia nerviosa (22).…”
Section: R Lineros-linero B Martínez-núñezunclassified
“…En 2014 se publica una revisión sobre los tratamientos en grupo de adolescentes con TCA, donde queda reflejado la escasez de estudios con un buen diseño en este ámbito. Se encontró que los grupos de terapia conductual cognitiva eran más efectivos para la bulimia nerviosa y la terapia grupal multifamiliar mostró ser prometedora para la anorexia nerviosa (22).…”
Section: R Lineros-linero B Martínez-núñezunclassified
“…Group work is often included in ED treatment settings (APA, 2006). Downey (2014) has suggested that increased research attention may be paid to the group modality considering its cost effectiveness and a shortage of available resources. In The Eating Disorder Sourcebook , Costin (2007) pointed out potentially helpful aspects of group work that include providing education, increasing support, building interpersonal relations, and managing confrontation.…”
Section: Treatment Strategiesmentioning
confidence: 99%